A region's basic image as a measure of its attractiveness - Vasilis Angelis; Katerina Dimaki (International Journal of Economic Sciences and Applied Research, 2011)
The growth or decline of a region depends on its power to pull and retain both business and the right blend of people to run them. This pulling power depends on what we call the Image of the region, a variable which expresses the region's present state of development and future prospects and may be defined as a function of a multitude of factors; economic, social and environmental ones. The Image of a region may prove a very useful tool for planning purposes, since it doesn't only give an early diagnosis of any possible changes, sometimes discontinuous, in the region's pattern of development, but it also indicates the reasons for those changes. Hence, it may be used as the basis for designing appropriate measures to assist a region's development. The objective of this paper is to define a region's image, based on an analysis of the business and the residential location process, to identify, through literature, the factors needed to quantify this image and finally, to suggest ways of measuring these factors.
Keywords: C02; C65; R58; 330; region's image; region's attractiveness; regional development